2022
DOI: 10.3390/molecules27103164
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Phytosterols into Androstenedione—A Technological Prospecting Study

Abstract: Androstenedione (AD) is a key intermediate in the body’s steroid metabolism, used as a precursor for several steroid substances, such as testosterone, estradiol, ethinyl estradiol, testolactone, progesterone, cortisone, cortisol, prednisone, and prednisolone. The world market for AD and ADD (androstadienedione) exceeds 1000 tons per year, which stimulates the pharmaceutical industry’s search for newer and cheaper raw materials to produce steroidal compounds. In light of this interest, we aimed to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…In recent reviews, the background of AD-producing strains, types of substrates and treatment methods, yield, and other information have been outlined in detail [ 1 , 6 ]. In order to show more clearly the effects of different cofactor regulation strategies and transformation system production technology on AD production, the production yield and productivity of MNR and recombinant strains constructed based on different cofactor regulation strategies were compared ( Table 2 ).…”
Section: Comparison Of the Influence Of Various Cofactor Regulation S...mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent reviews, the background of AD-producing strains, types of substrates and treatment methods, yield, and other information have been outlined in detail [ 1 , 6 ]. In order to show more clearly the effects of different cofactor regulation strategies and transformation system production technology on AD production, the production yield and productivity of MNR and recombinant strains constructed based on different cofactor regulation strategies were compared ( Table 2 ).…”
Section: Comparison Of the Influence Of Various Cofactor Regulation S...mentioning
confidence: 99%
“…C-19 steroids, especially AD, are the main raw materials for steroid hormone drugs. The global market for AD and ADD exceeds 1000 tons per year, and it is estimated that the global AD market will reach USD 210 million by 2025 [ 6 ]. Promoting the green, efficient, and low-cost production of C-19 steroids, such as AD, has become an important strategic demand for the global steroid pharmaceutical industry to achieve green, efficient production and sustainable development.…”
Section: Concentrations and Future Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…4AD is a highly valuable steroid precursor commonly used to produce a broad spectrum of therapeutically important hormones, such as testosterone and estradiol. Recently, 4AD synthesis via microbial sterol biotransformation has made considerable progress at the industrial scale. However, the starting substrates (sterols) need to be obtained from natural resources, and the low water solubility of sterols reduces their bioavailability during steroid production . In addition to classical biotransformation approaches, de novo steroid synthesis from simple carbon sources can be employed to obtain steroidal compounds in an environmentally friendly process. However, to the best of our knowledge, no studies regarding the microbial de novo synthesis of 4AD have been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…19−21 However, the starting substrates (sterols) need to be obtained from natural resources, and the low water solubility of sterols reduces their bioavailability during steroid production. 18 In addition to classical biotransformation approaches, de novo steroid synthesis from simple carbon sources can be employed to obtain steroidal compounds in an environmentally friendly process. 22−25 However, to the best of our knowledge, no studies regarding the microbial de novo synthesis of 4AD have been reported to date.…”
Section: ■ Introductionmentioning
confidence: 99%